THE ROLE OF CENTRAL ASIAN SCHOLARS IN THE SOCIO-POLITICAL LIFE OF THE REGION - Hafizullaev, Javlon (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
In the Middle Ages, the urban population — which constituted an important force in Central Asian society — did not participate in the system of state governance. Under such circumstances, scholars, relying on the support of the townspeople, emerged as a powerful political force within society. This article analyzes the role of scholars and, more broadly, representatives of intellectual life in Central Asian society.